Yield gap analysis in rice, wheat and pulses in India - Singh, Mahendra (Annals of Agricultural Research, 2014)
The study has critically examined the state-wise yield gap, correlation between state average yield, share of irrigated area and fertilizer consumption (kg/ha) in rice, wheat and pulses in major producing states. The farmers’ perception on state specific constraints in rice production are also analysed. The results showed that there were substantial yield gaps ranged from 4-60% in rice; 3-54% in wheat; and 6-202% in chickpea and pigeonpea between improved and check varieties at farmers’ field in major producing states. There are positive correlation between state average yield and seed replacement rate, share of irrigated area and fertilizer consumption in rice, wheat, chickpea and pigeonpea (except between state average yield and share of irrigated area under chickpea and pigeonpea crop). It is suggested that to bridge the yield gap in rice, wheat and pulses, there is need of district level information on seed replacement rate of these crops. If district with low seed replacement rate and lower yield need special attention for yield improvement by adoption of the improved varieties and it will be economical and suitable policy option to bridge the yield gap in these crops. If seed replacement rate is at desired level (25% for self pollinated crops and 35% for cross pollinated crops) emphasis should given to increase irrigated area and fertilizer consumption and identify the other constraints and judicious measures use to remove on the basis of severity of the constraints.